2017
DOI: 10.1002/nag.2702
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a three‐dimensional constitutive model for nonlinear site response and soil‐structure interaction analyses using centrifuge test data

Abstract: Summary The capability of a bounding surface plasticity model with a vanishing elastic region to capture the multiaxial dynamic hysteretic responses of soil deposits under broadband (eg, earthquake) excitations is explored by using data from centrifuge tests. The said model was proposed by Borja and Amies in 1994 (J. Geotech. Eng., 120, 6, 1051‐1070), which is theoretically capable of representing nonlinear soil behavior in a multiaxial setting. This is an important capability that is required for exploring an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This has motivated the development of more practical, yet still effective constitutive models that can reproduce the main features of dynamic soil behavior using only a small number of parameters. 31,[35][36][37] Among them, the bounding surface multiaxial plasticity model by Borja and Amies 31 (BA model) is one of the extensively used models, which has consistently shown good performance in small-scale applications studied to date [38][39][40] and therefore is adopted in this study to be used for large-scale ground motion simulation problems.…”
Section: Methodsmentioning
confidence: 99%
“…This has motivated the development of more practical, yet still effective constitutive models that can reproduce the main features of dynamic soil behavior using only a small number of parameters. 31,[35][36][37] Among them, the bounding surface multiaxial plasticity model by Borja and Amies 31 (BA model) is one of the extensively used models, which has consistently shown good performance in small-scale applications studied to date [38][39][40] and therefore is adopted in this study to be used for large-scale ground motion simulation problems.…”
Section: Methodsmentioning
confidence: 99%
“…A calibrated and validated nonlinear soil model with a viscous damping‐bounding surface plasticity model (NLV) 47 is also adopted in the nonlinear analyses. The parameters of the NLV model are set according to the soil properties—namely, the radius of the bounding surface is set as R ≈ 0.0235 G max , where G max is the initial shear modulus; parameters for the intensity of the hardening are set as h = 0.11 G max , m = 0.93; and the viscous damping coefficient is set as ξ 0 = 0.014.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Slip and normal behaviour of the soil-structure interface was simulated using the surface-to-node interface. An interface slip coefficient was defined as 0.7 tan(φ soil ), as used by Deng et al [34] and Zhang et al [35] to validate the numerical model. Tsinidis [7] reported that simulating only the slip and restraining the potential separation between the soil and tunnel produces an unrealistic transmission of the tensile stress to the soil in contact.…”
Section: Numerical Modelmentioning
confidence: 99%